Interrogating the role of the milk microbiome in mastitis in the multi-omics era - Couvillion, Sneha P.; Mostoller, Katie E.; Williams, Janet E.; Pace, Ryan M.; Stohel, Izabel L.; Peterson, Haley K.; Nicora, Carrie D.; Nakayasu, Ernesto S.; Webb-Robertson, Bobbie-Jo M.; McGuire, Mark A.; McGuire, Michelle K.; Metz, Thomas O. (Frontiers in Microbiology, 2023)
There is growing interest in a functional understanding of milk-associated microbiota as there is ample evidence that host-associated microbial communities play an active role in host health and phenotype. Mastitis, characterized by painful inflammation of the mammary gland, is prevalent amongst lactating humans and agricultural animals and is associated with significant clinical and economic consequences. The etiology of mastitis is complex and polymicrobial and correlative studies have indicated alterations in milk microbial community composition. Recent evidence is beginning to suggest that a causal relationship may exist between the milk microbiota and host phenotype in mastitis. Multi-omic approaches can be leveraged to gain a mechanistic, molecular level understanding of how the milk microbiome might modulate host physiology, thereby informing strategies to prevent and ameliorate mastitis. In this paper, we review existing studies that have utilized omics approaches to investigate the role of the milk microbiome in mastitis. We also summarize the strengths and challenges associated with the different omics techniques including metagenomics, metatranscriptomics, metaproteomics, metabolomics and lipidomics and provide perspective on the integration of multiple omics technologies for a better functional understanding of the milk microbiome.